THE CORRELATION BETWEEN DIET PATTERN AND LIFESTYLE ON DIABETES MELITUS RISK AT PUBLIC HEALTH CENTRE PEMBINA PALEMBANG IN 2016 - Mardiah; Labris Shandi (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2017)
Diabetes Mellitus is an autoimmune disease characterized by hyperglycemia secondary toreduced pancreatic insulin production, reduced insulin release in response to a carbohydrate load, ordisruption cellular response to insulin. The aim of this study to know the correlation between diet patternand lifestyle on diabetes melitus risk at Public Health Centre Pembina Palembang in 2016. This study useda survey design analytic through cross sectional approach. The population of this study were all patientswho come for treatment at Publich Health Centre Pembina Palembang in 2016, the total sample of thisstudy was 60 respondents. The result of analysis found that there are relationship of diet pattern ondiabetes melitus risk at public health centre Pembina Palembang in 2016 (ρ value = 0.013). There isrelationship of lifestyle on diabetes melitus risk at Public Health Centre Pembina Palembang in 2016 (ρvalue = 0.032). It is suggested to health officer should provide councelling and blood sugar level treatmentregularly, especially health centers, to prevent rising numbers of diabetes mellitus, especially in PublicHealth Centre Pembina Palembang